2018
DOI: 10.1021/jacs.8b03805
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Tryptophans as NMR Probes of Allosteric Coupling in Membrane Proteins: Application to the A2A Adenosine Receptor

Abstract: Tryptophan indole 15N–1H signals are well separated in nuclear magnetic resonance (NMR) spectra of proteins. Assignment of the indole 15N–1H signals therefore enables one to obtain site-specific information on complex proteins in supramacromolecular systems, even when extensive assignment of backbone 15N–1H resonances is challenging. Here we exploit the unique indole 15N–1H chemical shift by introducing extrinsic tryptophan reporter residues at judiciously chosen locations in a membrane protein for increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
(115 reference statements)
6
33
0
2
Order By: Relevance
“…In agreement with NMR studies [42,[61][62][63][64] and previous MD simulation data [44,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], comparison of A2aR crystal structures points to TM3, TM5, TM6 and TM7 as key receptoractivating helices. Therefore, we base our quantitative MD analysis of A2aR activation/modulation on the following metrics: TM3-TM5, TM3-TM6, TM3-TM7 distances; W246 6.48 χ1 dihedral angle change; TM3 and ECL2 vertical (Z-axial) movement; root mean square deviation (RMSD) of transmembrane domain (TMD), ECL2, TM6 and L95 3.43 .…”
Section: (S1 Fig) Both the Intermediate And Active Crystalssupporting
confidence: 89%
See 2 more Smart Citations
“…In agreement with NMR studies [42,[61][62][63][64] and previous MD simulation data [44,[65][66][67][68][69][70][71][72][73][74][75][76][77][78], comparison of A2aR crystal structures points to TM3, TM5, TM6 and TM7 as key receptoractivating helices. Therefore, we base our quantitative MD analysis of A2aR activation/modulation on the following metrics: TM3-TM5, TM3-TM6, TM3-TM7 distances; W246 6.48 χ1 dihedral angle change; TM3 and ECL2 vertical (Z-axial) movement; root mean square deviation (RMSD) of transmembrane domain (TMD), ECL2, TM6 and L95 3.43 .…”
Section: (S1 Fig) Both the Intermediate And Active Crystalssupporting
confidence: 89%
“…Despite current knowledge, to date, only one selective A2aR agonist (Regadenoson) has gained FDA approval, as well as an antagonist (Istradefylline), which in combination with levodopa is used for the treatment of Parkinson's disease in Japan [58,59]. A2aR is an ideal system to study GPCR activation processes because it has a high propensity for binding lipid allosteric modulators [60], is a well-known drug target for several agonists and antagonists, and has been the focus of recent NMR studies [42,[61][62][63][64]. These studies show that, upon the addition of a full agonist, A2aR activation follows outward movements of TM5 and TM6 (including rotation in the latter), an inward shift of the intracellular part of TM7, and a vertical translation of TM3 [42,[61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present quantitative description of A 2A AR structural ensembles by 19 F-NMR probes complements a recent qualitative many-parameter overview of A 2A AR structural plasticity by high-resolution NMR, which revealed that there are structural manifolds linked to function (16,17). The 19 F-NMR spectra observed for probes in TM VI and TM VII are qualitatively similar, but only the spectra TM VII are sufficiently well resolved to enable quantitative measurements, due to the location of the -CF 3 group near aromatic residues that reflect the efficacy of bound drugs.…”
Section: Discussionsupporting
confidence: 70%
“…In earlier high-resolution NMR studies of stable-isotope-labeled A 2A AR, NMR observations afforded a global view of structural plasticity throughout the 3D structure, and changes in conformational equilibria could be related to variable drug efficacies and to inactivation of an allosteric switch (16,17). To characterize these structure ensembles in greater detail and to quantify rates of exchange among the different conformers, we now used 19 F-NMR with single extrinsic probes judiciously placed in positions at the intracellular tips of the transmembrane helices (TM) VI, VII, and VIII.…”
mentioning
confidence: 99%